Technical method in passive cooling for photovoltaic panels using phase change material - Ahmad Al Miaari; Hafiz Muhammad Ali (Case Studies in Thermal Engineering, 2023)
A small percentage of the energy from solar radiation is converted into electricity by the photovoltaic module, while the rest is lost as heat. This heat causes the module's temperature to increase effecting its performance and decreasing its efficiency. To address this problem, a 20 Watt photovoltaic module cooled using phase change material was analyzed. The phase change material improves module performance and efficiency by absorbing the heat and storing it as sensible and latent heat during the day. The traditional method in such systems is to seal the photovoltaic panels rare back and fill it with phase change material for cooling. In this study, six small containers filled with phase change material that are easy to assemble and disassemble are employed instead of a single container filled with phase change material.This makes the application more technically applicable. The adopted method has several advantages over previous approaches. It allows for convenient adjustment of the phase change material to effectively adapt to weather fluctuations. Furthermore, when the phase change material inside the container is completely dissolved, the container itself can be easily replaced, improving the cooling process and enhancing the efficiency of the photovoltaic system throughout the day. Moreover, the containers tackle the issue of phase change material leakage which has been a persistent problem in many studies Additionally, it offers the advantage of reducing the required amount of phase change material by eliminating the need to fill the entire back of the system. The goal of this study is to reevaluate the passive cooling method for photovoltaic panels using phase change material and investigate the effect of these containers while being filled with appropriate and inappropriate phase change material properties on the temperature and performance of the photovoltaic module. The measurements were taken using three temperature sensors at different locations for cooled and non-cooled photovoltaic modules. The experimental results revealed that using appropriate phase change material can reduce the average temperature of the photovoltaic module by 10 °C, and enhance the power performance by 5.23% compared to the non-cooled photovoltaic modules. Moreover, results showed a negative impact on the temperature and performance of the module when using inappropriate phase change material were it can reduce the power of the module by 3 W compared to the non-cooled module.